Tipologi Tipologi Rumah Pacenan Situbondo, Jawa Timur Berdasar Gender - Agustin, Selvia Noer; Widiastuti, . (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2024)
Pacenan houses are examples of vernacular architecture in Situbondo Regency, East Java Province. The lack of writing on this form of homes has encouraged authors to study them and to develop a typology of  pacenan’s vernacular architecture based on gender. This study implements a qualitative approach supported by case studies of pacenan houses in Tanjung Pecinan Village, Mangaran District, and Situbondo Regency. The latest location is seen as the origin of the pacenan house. At first, an analysis of layout/spatial division and how spaces are zoned based on uses by male and female users is performed. Then, houses are grouped based on architectural differences. This activity is carried out by producing plans and three-dimensional drawings of all houses included in the study. This research develops two underlying considerations to be used to develop gender-based typologies: considerations regarding layout/spatial division and considerations about the overall existence of houses. Based on the layout, there are two typologies: female spaces that include an amper, roma , and kitchen, all of these spaces are part of the indoor formation. Male spaces consist of rangghun, langgar and tanean lanjhang . These are all located outside the houses. Then, based on the overall existence of houses, there are also two typologies. The first is based on the existence of distance between mothers’ houses and daughters’ houses. The second is based on the existence of langgar . Keywords: typology; pacenan house; Situbondo; East Java; gender   Abstrak Rumah pacenan adalah salah satu contoh arsitektur vernacular di Kabupaten Situbondo, Propinsi Jawa Timur. Minimnya tulisan tentang wujud rumah pacenan telah mendorong penulis untuk menstudi serta membangun tipologinya berdasarkan pertimbangan gender. Metode yang digunakan adalah kualitatif didukung oleh studi kasus dari beragam rumah pacenan yang berlokasi di Desa Tanjung Pecinan, Kecamatan Mangaran, dan Kabupaten Situbondo. Lokasi terakhir dipandang sebagai daerah asal kelahiran rumah pacenan . Di awal dilaksanakan analisis layout rumah pacenan yang dizone berdasar pemanfaatannya oleh pengguna lelaki dan/atau perempuan. Kemudian dilakukan pengelompokan tipe rumah yang berbeda. Kegiatan ini dilaksanakan dengan memproduksi denah dan gambar tiga dimensi dari semua rumah yang menjadi bagian studi. Penelitian ini menunjukan dua dasar pertimbangan yang bisa dipakai membangun tipologi rumah pacenan berbasis gender, yaitu: pertimbangan terkait layout-divisi ruang dan pertimbangan terkait eksistensi rumah secara keseluruhan. Berdasarkan layout, dibangun dua tipologi ruang, yaitu: ruang perempuan yang terdiri dari  amper, roma dan dapur, ruang-ruang ini berada di dalam rumah. Dan ruang lelaki yang terdiri dari rangghun, langgar dan tanean lanjhang . Semua ruang ini berada di luar rumah. Berdasarkan wujud rumah secara keseluruhan dibangun dua tipologi. Tipologi pertama didasari oleh keberadaan jarak antara rumah ibu dan rumah anak perempuan. Tipologi kedua didasari atas keberadaan langgar . Kata kunci: tipologi; rumah pacenan; Situbondo; Jawa Timur; gender